(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Utilizing household kitchen waste is one of the strategic solutions to reduce the volume of organic waste while supporting environmentally friendly agriculture. This activity aims to describe the process of converting kitchen waste from the residents of Lubuk Banjar Village into liquid organic fertilizer (LOF) through an integrated waste management system and its application to planting red shoot trees. The methods used include socialization of organic waste management, training on making LOF using kitchen waste, and applying LOF to red shoot plants as a form of direct implementation in the community. Data were obtained through observation, documentation, and evaluation of plant growth results after the application of LOF. The results of the activity indicate that the community is capable of processing kitchen waste into liquid organic fertilizer (POC) independently, and the application of POC has a positive impact on the growth of red-tip plants, such as improving soil fertility and better leaf development. This activity not only contributes to reducing environmental pollution caused by organic waste but also increases community awareness and participation in sustainable waste management. Thus, the utilization of kitchen waste into POC through an integrated waste management system can be an effective and sustainable alternative solution for the residents of Lubuk Banja Village.